Meditations - Marcus Aurelius Emperor of Rome 121-180 (Modern Library classics., 2003)
A new translation, the first in thirty-five years, of one of the most influential and admired books of the ages, the reflections of Marcus Aurelius, Stoic philosopher and emperor of Rome 161-180 A.D., few books have meant as much to as many as Marcus Aurelius's Meditations. It remains a life-enhancing work of the basics of Stoic doctrine, Aurelius's life and career, the recurring themes and structure of the work's ongoing influence.